2022
DOI: 10.3389/fpsyg.2021.781669
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Challenges in the Measurement of Constructs Underlying Criminal Responsibility in Children and Young Adults: A Cross-Sectional Study

Abstract: At present, many countries have lowered the minimum age of criminal responsibility to deal with the trend of juvenile crime. In practical terms, whether countries advocate for lowering the age of criminal responsibility along with early puberty, or regulating the minimum age of juvenile criminal responsibility through their policies, their deep-rooted hypothesis is that age is tied to adolescents’ psychological growth, and, with the rise in age, the capacity for dialectical thinking, self-control, and empathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…This leads to a ‘time gap’ which leaves middle adolescents most prone to commit crimes (Walsh, 2011). This finding is confirmed by a recent study conducted in China, which shows that the self‐control ability of children continuously decreases from the ages of eleven to 15 years, and then U‐turns to a rising trend (Shang et al., 2022). Therefore, even adopting the UN Committee on the Rights of the Child, 2019, General Comment No.24's recommendation to set the MACR at 14 years, arguably it still fails to protect the most vulnerable group of middle adolescents, at around 15 years of age, which has the weakest ability to exercise self‐control.…”
Section: The Classic Dilemma In Fixing the Macr: Either Convicting Th...supporting
confidence: 73%
“…This leads to a ‘time gap’ which leaves middle adolescents most prone to commit crimes (Walsh, 2011). This finding is confirmed by a recent study conducted in China, which shows that the self‐control ability of children continuously decreases from the ages of eleven to 15 years, and then U‐turns to a rising trend (Shang et al., 2022). Therefore, even adopting the UN Committee on the Rights of the Child, 2019, General Comment No.24's recommendation to set the MACR at 14 years, arguably it still fails to protect the most vulnerable group of middle adolescents, at around 15 years of age, which has the weakest ability to exercise self‐control.…”
Section: The Classic Dilemma In Fixing the Macr: Either Convicting Th...supporting
confidence: 73%
“…This leads to a 'time gap' which leaves middle adolescents most prone to commit crimes (Walsh, 2011). This finding is confirmed by a recent study conducted in China, which shows that the self-control ability of children continuously decreases from the ages of eleven to 15 years, and then U-turns to a rising trend (Shang et al, 2022). Therefore, even adopting the UN Committee on the Rights of the Child, 2019, General Comment No.24's recommendation to set the MACR at 14 years, arguably it still fails to protect the most vulnerable group of middle adolescents, at around 15 years of age, which has the weakest ability to exercise self-control.…”
Section: The Classic Dilemma In Fixing the Macr: Either Convicting Th...supporting
confidence: 56%
“…This data came from the empirical study of the age growth of teenagers’ three capacity for criminal responsibility conducted by Professor Shang Y’s team of Shandong Normal University. After a preliminary overall selection and two supplementary selections, the study involved students from junior to senior three in S County, as well as some first-year students from S University, S Province, China, finally selecting a sample of 3,208 people ( Shang et al, 2022 ). Then, we excluded 759 samples of students over the age of 18, remaining 2,449 samples for our research.…”
Section: Methodsmentioning
confidence: 99%
“…In 2022, an empirical study on 3,208 junior high school, senior high school and freshman students in S Province of the People's Republic of China showed that although age variables have significant effects on dialectical thinking ability, self-control ability and empathy ability, only empathy ability has a trend of strengthening with the increase of age. However, recognition ability and control ability were negatively correlated with age variables (Shang et al, 2022). Therefore, it is impossible to understand the overall development of juvenile ability of responsibility solely through the growth of age.…”
Section: The Current Studymentioning
confidence: 99%